Effects of hydroxyapatite/Zr and bioglass/Zr coatings on morphology and corrosion behaviour of Rex-734 alloy - Say, Y.; Aksakal, B. (SPRINGER, 2016)
To improve corrosion resistance of metallic implant surfaces, Rex-734 alloy was coated with two different bio-ceramics; single-Hydroxyapatite (HA), double-HA/Zirconia(Zr) and double-Bioglass (BG)/Zr by using sol-gel method. Porous surface morphologies at low crack density were obtained after coating and sintering processes. Corrosion characteristics of coatings were determined by Open circuit potential and Potentiodynamic polarization measurements during corrosion tests. Hardness and adhesion strength of coating layers were measured and their surface morphologies before and after corrosion were characterized by scanning electron microscope (SEM), XRD and EDX. Through the SEM analysis, it was observed that corrosion caused degradation and sphere-like formations appeared with dimples on the coated surfaces. The coated substrates that exhibit high crack density, the corrosion was more effective by disturbing and transmitting through the coating layer, produced CrO3 and Cr3O8 oxide formation. It was found that the addition of Zr provided an increase in adhesion strength and corrosion resistance of the coatings. However, BG/Zr coatings had lower adhesion strength than the HA/Zr coatings, but showed higher corrosion resistance.
Keywords: SOL-GEL COATINGS; STAINLESS-STEEL; AISI 316L; TITANIUM; IMPLANT; SS; Engineering; Materials Science